The effectiveness of green betel leaf (Piper bettle Linn) extract hand sanitizer gel in reducing bacterial colonies on the palm hand of dental clinical clerkship student: Efektivitas gel hand sanitizer ekstrak daun sirih hijau (Piper bettle Linn) mengurangi koloni bakteri pada telapak tangan mahasiswa kepaniteraan klinis kedokteran gigi - Hendry Rusdy; Abdullah Oes; Olivia Avriyanti Hanafiah; Rahmi Syaflida; Arin Pratiwi Nasution (Makassar Dental Journal, 2021)
Objective: To determine the effectiveness of using green betel leaf (Piper bettle Linn) extract hand sanitizer gel in reducing the number of bacterial colonies in the palms of hand. Method: In this experimental research with posttest only with control group de-sign using dental clinical clerkship students of Faculty of Dentistry Universitas Sumatera Utara. They were evenly divided into 5 groups. They were chlorhexidine gel (group 1), 1% green betel leaf extract (group 2), 3% green betel leaf extract (group 3), 5% green betel leaf extract (group 4), and use of placebo (group 5). Bacterial colonies isolated from the swabs were identified by stan-dard microbiological procedures. All statistical analysis methods were conducted using the one-way Anova and posthoc LSD tests. Results: The results of univariate analysis showed that sig <0.05, meaning that there was a difference in the number of bac-terial colonies between chlorhexidine, 1%, 3%, and 5% green betel extract gel. The one-way Anova test at 95% confidence level proved that the differences are significant at p-value 0,001. Conclusion: There is a difference in the effectiveness of using a hand sanitizer for green betel leaf extract on the number of bacterial colonies in the palms of hand. Hand sanitizer green betel leaf extract gel 5% more effective than 1% and 3% concentrations.